Plattenumbau; Transformation of a prefabricated panel building - Schwarz, Marlene (My University, 2026)
Prefabricated mass social housing buildings, known in German as Plattenbau, are the face of GDR (Deutsche Demokratische Republik) cities. They are the legacy of a country that no longer exists. Built in the 1970s, they are the consequence of engineers and architects' research on extreme standardisation of construction. After World War II, prefabrication was presented as the solution to house as many people as possible in good conditions across Europe. Taking a close look at the Plattenbau heritage reflects the question of collective memory. Since German reunification in 1989, far from their original appeal, they illustrate the failure of Soviet modernism. Today, more than one million units stand vacant, and entire districts are being demolished. The discrediting of these modern buildings is unreasonably blamed on their architectural features, and this unwanted heritage has, since the fall of the Iron Curtain, been hastily erased from the surface of the earth to make space for other types of housing. Housing is a human right, yet Europe is still facing a housing crisis. This thesis aims to expose the qualities of the Plattenbau as a resource to provide homes. By understanding the utopian ideology behind prefabrication and the development of living norms, it is possible to recognise the spatial and living qualities provided by this architectural legacy on one hand and the negative impact it had on societies on the other. Furthermore, the thesis also examines the spatial impact caused by demographic shrinkage. Indeed, uneven demographic changes have an impact on small and medium size towns of the former DDR. They lead, for example, to the under-usage or vacancy of standing buildings. The two mass social housing districts, built in 1975 next to the Hanseatic city of Stendal, are a striking example of the challenges former East German middle-sized cities are facing nowadays. This work presents both the availability of empty Plattenbau prone to demolition and the shrinking cities phenomenon as incredible opportunities for our generation of architects to think about housing in a post-growth European context. It explores through architectural and spatial interventions the possibility of regenerating Plattenbau as comfortable and spacious homes, following Renée Gailhoustet’s theory of living spaces. The buildings are seen as a composition of removable and movable prefabricated components. In a shrinking city context, the method used is the de-densification of the existing building by removing components and introducing a mixed-use program of living and working environments in the middle of nature. The result of the project aims to show the potential of Plattenbau for transformation.